2020
DOI: 10.5194/amt-2020-233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determination of Aethalometer multiple-scattering enhancement parameters and impact on source apportionment during the winter 2017–2018 EMEP/ACTRIS/COLOSSAL campaign in Milan

Abstract: Abstract. In the frame of the EMEP/ACTRIS/COLOSSAL campaign in Milan during winter 2018, equivalent black carbon measurements using the Aethalometer 31 (AE31), the Aethalometer 33 (AE33), and the Multi-Angle Absorption Photometer (MAAP) were carried out together with levoglucosan analyses on 12-h resolved PM2.5 samples collected in parallel. From AE31 and AE33 data, the loading-corrected aerosol attenuation coefficients (bATN) were calculated at 7 wavelengths (λs, where λ = 370, 470, 520, 590, 660, 880, 950 nm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…S3). The values of the C factor for the AE33 TFE-coated glass and M8060 filter tapes obtained at urban background stations in Rome (Valentini et al, 2020a) and Leipzig (Müller, 2015;Bernardoni et al, 2020) were in the same range as those found in this work for BCN (Table 1).…”
Section: Multiple Scattering Correction Factor: Average Values and Sesupporting
confidence: 81%
See 2 more Smart Citations
“…S3). The values of the C factor for the AE33 TFE-coated glass and M8060 filter tapes obtained at urban background stations in Rome (Valentini et al, 2020a) and Leipzig (Müller, 2015;Bernardoni et al, 2020) were in the same range as those found in this work for BCN (Table 1).…”
Section: Multiple Scattering Correction Factor: Average Values and Sesupporting
confidence: 81%
“…Moreover, a wavelength-dependent C factor can have an impact on aethalometer based BC source apportionment analysis, such as the Aethalometer model, used to determine the contribution from fossil fuels vs biomass burning emissions (Sandradewi et al, 2008). Weingartner et al (2003) and Segura et al (2014) found no wavelength dependence for the multiple scattering parameter C for older versions of aethalometer (model AE31), whereas Bernardoni et al (2020) found a decrease of the C factor with wavelengths, although not statistically significant, and reported the impact of the wavelength dependent C on source apportionment model results. Virkkula et al (2015) and Drinovec et al (2017) have shown that the AE33 factor loading parameter, k, increases with increasing BF (smaller particles) and decreases with increasing SSA and that the wavelength dependence of k also depends on these two optical properties.…”
Section: Wavelength Dependence Analysis From the Pp_unimi Vs Ae33 Commentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly a constant value is used appropriate for the instrument and filter material. It is to be noted that the Cref value can have a large variability depending on seasons, location, and methodology of determination (Collaud Coen et al, 2010;Backman et al, 2017;Di Biagio et al, 2017;Bernardoni et al, 2021;. The scattering correction requires measurement of the scattering coefficient which in many cases is not possible due to the lack of instrumentation and this correction is assumed to be unity as in this study.…”
Section: Measurement Methodsmentioning
confidence: 99%